Matrix-dependent regulation of AKT in hepsin-overexpressing PC3 prostate cancer cells - Wittig-Blaich, Stephanie Maritta; Kacprzyk, Łukasz Antoni; Eismann, Thorsten; Bewerunge-Hudler, Melanie; Kruse, Petra; Winkler, Eva; Strauss, Wolfgang S L; Hibst, Raimund; Steiner, Rudolf; Schrader, Mark; Mertens, Daniel; Sültmann, Holger; et al. (Neoplasia, 2011)
The serine-protease hepsin is one of the most prominently overexpressed genes in human prostate carcinoma. Forced expression of the enzyme in mice prostates is associated with matrix degradation, invasive growth, and prostate cancer progression. Conversely, hepsin overexpression in metastatic prostate cancer cell lines was reported to induce cell cycle arrest and reduction of invasive growth in vitro. We used a system for doxycycline (dox)-inducible target gene expression in metastasis-derived PC3 cells to analyze the effects of hepsin in a quantitative manner. Loss of viability and adhesion correlated with hepsin expression levels during anchorage-dependent but not anchorage-independent growth. Full expression of hepsin led to cell death and detachment and was specifically associated with reduced phosphorylation of AKT at Ser473, which was restored by growth on matrix derived from RWPE1 normal prostatic epithelial cells. In the chorioallantoic membrane xenograft model, hepsin overexpression in PC3 cells reduced the viability of tumors but did not suppress invasive growth. The data presented here provide evidence that elevated levels of hepsin interfere with cell adhesion and viability in the background of prostate cancer as well as other tissue types, the details of which depend on the microenvironment provided. Our findings suggest that overexpression of the enzyme in prostate carcinogenesis must be spatially and temporally restricted for the efficient development of tumors and metastases.
Available online 4 March 2014
Gesehen am 21.11.2022